Associations of Early Age of First Intoxication with Past Year Drinking Contexts and Problems. (7th June 2019) - Lipperman-Kreda, Sharon; Grube, Joel W.
Abstract: Background : Mechanisms underlying associations between early drinking and problems are largely unknown. Objectives : We investigated (a) associations between early age of first intoxication (≤15 years) and past year drinking in different contexts and (b) whether early age of first intoxication is differentially associated with problems in these contexts. Methods : We used survey data collected in 2013–2014 from 405 past-year adolescent drinkers in 24 midsized California cities. Data included demographics; drinking behaviors; age of first intoxication; frequency of being at and drinking at restaurants, bars/nightclubs, outdoor places, and home; and problems. We used multilevel logistic and negative binomial models to account for the clustering of adolescents within cities. Probabilities were corrected to maintain family-wise error rates. Results : Early age of first intoxication was associated with a 120% increase in the odds of drinking at outdoor settings (OR = 2.20, pc < .05). Early age of first intoxication was associated with increased numbers of problems related to drinking in restaurants (IRR = 5.72, pc < .001), outdoor settings (IRR = 3.40, pc < .001), and homes (IRR = 2.84, pc < .001). Later intoxication (≥16 years) was not significantly associated with increased drinking or problems in any of these contexts. Conclusions : Results suggest that underage drinkers who report early intoxication are more likely to drink at outdoor settings, but not other contexts. However, they may differentially experience drinking problems across contexts. To target youths who have experienced intoxication at an early age and to reduce problems, prevention interventions should focus on outdoor settings.